Polymorphisms in circadian rhythm genes and the risk of differentiated thyroid cancer - Berrandou, Takiy-Eddine; Cordina-Duverger, Emilie; Mulot, Claire; Guizard, Anne-Valérie; Schvartz, Claire; Laurent-Puig, Pierre; Zidane, Monia; De Vathaire, Florent; Guénel, Pascal; Truong, Thérèse (Frontiers in Genetics, 2025)
Introduction:Circadian rhythms are controlled by biological clocks regulated at the molecular level by a set of circadian genes operating through a negative feedback loop. These genes also regulate key biological processes, including cell proliferation, cell cycle, and apoptosis.Methods:We investigated the role of circadian gene polymorphisms in the risk of differentiated thyroid cancer (DTC) and their interaction with DTC risk factors. Data were obtained from 463 DTC cases and 482 unrelated controls of European ancestry, selected from two population-based case-control studies conducted in France. Associations with 570 single nucleotide polymorphisms (SNPs) in 23 circadian genes were evaluated using multivariate logistic regression models. Gene- and pathway-level associations and gene–environment interactions were analyzed using the adaptive rank truncated product (ARTP) method.Results and discussion:We found no significant association between DTC risk and circadian gene polymorphisms at the SNP, gene, or pathway levels. However, we observed statistically significant interactions between smoking status and SNPs rs11204897 (RORC) and rs1012477 (PER3), as well as with the PER3 gene and the overall circadian pathway. These results suggest that smoking status may modulate the association between DTC and polymorphisms in circadian genes. Further studies are needed to confirm these findings.